Arbutin Alleviates the Liver Injury of α-Naphthylisothiocyanate-induced Cholestasis Through Farnesoid X Receptor Activation - Wu, Peijie; Qiao, Ling; Yu, Han; Ming, Hui; Liu, Chao; Wu, Wenjun; Li, Baixue (Frontiers in Cell and Developmental Biology, 2021)
Cholestasis is a kind of stressful syndrome along with liver toxicity, which has been demonstrated to be related to fibrosis, cirrhosis, even cholangiocellular or hepatocellular carcinomas. Cholestasis usually caused by the dysregulated metabolism of bile acids that possess high cellular toxicity and synthesized by cholesterol in the liver to undergo enterohepatic circulation. In cholestasis, the accumulation of bile acids in the liver causes biliary and hepatocyte injury, oxidative stress, and inflammation. The farnesoid X receptor (FXR) is regarded as a bile acid–activated receptor that regulates a network of genes involved in bile acid metabolism, providing a new therapeutic target to treat cholestatic diseases. Arbutin is a glycosylated hydroquinone isolated from medicinal plants in the genus Arctostaphylos, which has a variety of potentially pharmacological properties, such as anti-inflammatory, antihyperlipidemic, antiviral, antihyperglycemic, and antioxidant activity. However, the mechanistic contributions of arbutin to alleviate liver injury of cholestasis, especially its role on bile acid homeostasis via nuclear receptors, have not been fully elucidated. In this study, we demonstrate that arbutin has a protective effect on α-naphthylisothiocyanate–induced cholestasis via upregulation of the levels of FXR and downstream enzymes associated with bile acid homeostasis such as Bsep, Ntcp, and Sult2a1, as well as Ugt1a1. Furthermore, the regulation of these functional proteins related to bile acid homeostasis by arbutin could be alleviated by FXR silencing in L-02 cells. In conclusion, a protective effect could be supported by arbutin to alleviate ANIT-induced cholestatic liver toxicity, which was partly through the FXR pathway, suggesting arbutin may be a potential chemical molecule for the cholestatic disease.